Kretivitas Kepala Madrasah dalam Meningkatkan Akhlak dan Prestasi Siswa di MA Al-Muhsin Pijot - Nasrullah (Pendidikan Al-Gafari, 2023)
Moral education is certainly important for all levels of education, from elementary school to university. In general, moral education is actually needed from an early age to become a leader. This study aims, First, to find out the strategy of the head of the madrasa in managing the moral education of students at MA Al-Muhsinin Pijot. Second, to find out what are the supporting and inhibiting factors in improving student morals and achievement at MA Al-Muhsinin Pijot. This study uses a qualitative approach. Data collection methods used by researchers include: Observation, interviews, and documentation. The research findings show that: First; a) reading the prayer reciting the yellow book together at the mosque, b) scholarship program, c) tahfis al qur'an, d) dhuha prayer in congregation before class, e) holding midday prayer in congregation at school, f) commemoration of holidays Islam, Second; The principal's strategic steps in building a religious culture at MA Al-Muhsinin Pijot are: through programs, planning, providing examples, partnerships and contributing to activities, habituation and evaluation. Third; Supporting and inhibiting factors in improving student morals and achievement in MA AL–Muhsinin Pijot, a) supporting factors, in increasing student morals and achievement are curriculum and learning, madrasa institutional organization, facilities and infrastructure, manpower (teachers and staff), financing, and community roles. b) the inhibiting factor in improving student morals and achievement at MA Al–Muhsinin Pijot is the number of skilled teachers, the background of students is less supportive. Efforts to improve morals and student achievement must be addressed together so that there are changes that occur in madrasas so as to create superior madrasas.